2014
DOI: 10.1105/tpc.114.130252
|View full text |Cite
|
Sign up to set email alerts
|

BBX19 Interacts with CONSTANS to RepressFLOWERING LOCUS TTranscription, Defining a Flowering Time Checkpoint inArabidopsis   

Abstract: The timely transition of vegetative to reproductive development is coordinated through quantitative regulation of floral pathway genes in response to physiological and environmental cues. Here, we show that the circadian-controlled expression of the Arabidopsis thaliana floral transition regulators FLOWERING LOCUS T (FT) and CONSTANS (CO) is antiphasic to that of BBX19, a transcription factor with two B-Box motifs. Diminished expression of BBX19 by RNA interference accelerates flowering, and constitutive expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(158 citation statements)
references
References 66 publications
4
141
0
1
Order By: Relevance
“…We have also demonstrated that lightgrown ceh1 (for constitutively expressing HPL) mutant plants accumulating high MEcPP levels are severely dwarfed (Xiao et al, 2012). Microarray analyses in conjunction with quantitative PCR identified a number of genes with robustly altered transcript levels in ceh1, among them BBX19, whose expression level is reduced by half (Xiao et al, 2012;Wang et al, 2014). The altered expression level of BBX19 and the severe dwarfism of ceh1 in conjunction with the reported function of BBX19 as a negative regulator of photomorphogenesis prompted us to explore the mode of action of this transcriptional regulator in plant photomorphogenic development.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…We have also demonstrated that lightgrown ceh1 (for constitutively expressing HPL) mutant plants accumulating high MEcPP levels are severely dwarfed (Xiao et al, 2012). Microarray analyses in conjunction with quantitative PCR identified a number of genes with robustly altered transcript levels in ceh1, among them BBX19, whose expression level is reduced by half (Xiao et al, 2012;Wang et al, 2014). The altered expression level of BBX19 and the severe dwarfism of ceh1 in conjunction with the reported function of BBX19 as a negative regulator of photomorphogenesis prompted us to explore the mode of action of this transcriptional regulator in plant photomorphogenic development.…”
Section: Introductionmentioning
confidence: 75%
“…We have previously established that mutant Arabidopsis plants (ceh1) accumulating high levels of the stress-specific retrograde signal MEcPP are dwarfed and have reduced BBX19 transcript levels (Xiao et al, 2012;Wang et al, 2014). The reported role of BBX19 in promoting hypocotyl growth (Kumagai et al, 2008) prompted us to examine its function in ceh1 as compared with the Columbia-0 (Col-0) wild-type plants.…”
Section: Bbx19 Is a Suppressor Of Photomorphogenesismentioning
confidence: 99%
“…BBX proteins exist in species from algae, mosses, animals, and plants and are functionally diverse (15,16). The founding and best-characterized member of the B-box family is CO. Studies have reported that other members of the BBX family such as COL3/BBX4, BBX6, BBX7 (COL9), BBX19, BBX24/SALT TOLERANCE (STO), microProtein1a (MiP1a)/ BBX31 and BBX32/EMBRYONIC FLOWER-1 INTER-ACTING PROTEIN6 (EIP6) also affect flowering with distinct mechanisms (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…which positively regulate the expression of other floral integrator genes such as SOC1, AGL24, FUL, AP1 and LFY at the shoot apex Jung et al, 2011;Yu et al, 2012;Wang et al, 2014). miR172 levels, unlike miR156, are regulated by SPL9 and SPL10, the effect of which modifies TOE1 and TOE2.…”
Section: Microrna Regulation Of Flowering and Plant Agementioning
confidence: 99%